Tensões da matemática como conhecimento: instrumentalização e formação do homem autônomo - Braga, Laudelina (2014)
This dissertation, of the search line Fundamentals of Educational Processes, in the studies field between philosophy and education, investigates the concept of autonomy and its possible implications for the question of the meaning and tensions of mathematics as knowledge. This study, which is structured in three chapters, discusses the tensions of mathematics as knowledge, instrumentality and formation of autonomous men, as well investigates the meaning of education and mathematical knowledge. Then, it analyzes the implications of autonomy and instrumentality in mathematics as knowledge today. The instrumental perspective complicates the interrogation and questioning. We leave to ask what is the arkhé, what students are indeed learning and how they are learning. Today the school is concerned mainly with the operationalization of education in order to train competent individuals to the labor market. However, with the proposal to discuss the tensions for the formation of an autonomous man, such situation requires changes and urgent investigations. In the context of tensions that are established in education and, more specifically, in the mathematical knowledge, a question imposes itself as decisive and, as the formal aspect, this research aims to reflect it: The meaning of mathematical knowledge present in schools and resizings of the current education promotes autonomy or the instrumentalization of the students? The goal is to discuss how the question of autonomy was thought in the history of Greek education and in the present day and, shortly thereafter, the challenges for the promotion of this autonomy in the learning and teaching process of mathematics. The methodological fundamentals of literature will enable the questioning, reflection and understanding of the reality that are being studied, in other words, of the teaching of mathematics.